The Relation between International Accounting Reporting Standard (IFRSs/IAS s) AndQualitative Characteristics Of Accounting information Study State in Branches of Foreign banks in Erbil governorate - Hawar Ghafur Hamadamin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The application of international standards contributes to improve the quality of the accounting information provided to the beneficiary parties through relevant, understandable, comparable, and highly reliable information. Banks have a special nature, both in terms of their activities and risks they face. This has led the international committees to establish independent standards for disclosure, presentation, and accounting measurement in their financial reports and statements; these offer a necessary input that helps the decision makers to assess the banks’ financial positions and results. The application of the International Financial Reporting Standards (IFRSs/IASs) in banks helps to standardize the preparation of financial statements and disclosures in line with the methods of preparation, presentation, and disclosure in which used by international banks.